TELEMEDICINE TECHNOLOGY: REDEFINING HEALTH SERVICES IN A PANDEMIC ERA - Loso Judijanto; Herlina Lidiyawati; Lola Yustrisia (Jurnal Kesehatan, 2024)
The COVID-19 pandemic has been a turning point for the global healthcare system, driving the rapid and extensive adoption of telemedicine technology. The study aims to evaluate the impact of telemedicine technology in responding to pandemics and its potential in healthcare reform. Through a systematic study of literature on articles, books and other documents, the study investigates the application of telemedicine in a variety of healthcare contexts, including chronic disease management, primary consultation, and triasis of COVID-19 patients. The results show that telemedics has successfully facilitated the continuity of health care in pandemic conditions, reduced the burden on health facilities, and minimized the risk of virus spread. The use of telemedicine also extends access to health care especially for patients in remote areas or with limited mobility. Furthermore, it was found that technological innovations and regulations that support telemedicine have accelerated its integration into the health system. Despite challenges, such as data security issues and limitations in physical inspections, innovative solutions and policy frameworks have been developed to overcome such obstacles. The study recommends increased investment in telemedicine technology and training for health professionals as a long-term strategy to improve the resilience of health systems.